Central Sensitization Symptom Severity and Patient-Provider Relationships in a Community Setting. (July 2021) - Wang, Xiao Jing; Ebbert, Jon O.; Gilman, Elizabeth A.; Rosedahl, Jordan K.; Ramar, Priya; Philpot, Lindsey M.
Introduction: Central sensitization syndromes (CSS) comprise an overlapping group of clinical conditions with the core feature of "pain arising as a direct consequence of a lesion or disease affecting the somatosensory system." Patients with CSS are known to have challenging interactions with healthcare providers contributing to psychological distress and increased healthcare utilization. CSS symptom severity has been associated with psychologic comorbidities, but little is known about how symptom severity relates to provider interactions. Methods: We performed a cross-sectional survey among patients with CSS in our primary care practices to examine the relationship between CSS symptom severity and experiences with doctors. Results: A total of 775 respondents completed the survey (775/5000; 15.5%) with 72% reporting high CSS symptom severity. About 44% of respondents had a prior diagnosis of fibromyalgia, 72% had migraines, and 28% had IBS. Patients with high CSS symptom severity were more likely to report that doctor(s) had often/always told them that they don't need treatment when they feel like they do (OR = 3.6, 95% CI 1.9-7.5), that doctor(s) often/always don't understand them (OR = 3.1, 95% CI 1.9-5.4), and that doctor(s) often/always seem annoyed with them when compared with respondents with low-moderate CSS symptom severity (OR = 4.8, 95% CI 2.2-12.5). Patients with high CSS symptom severity were at greater than 5 times odds of reporting being told that their symptoms were "all in their head" when compared to patients with low-moderate symptom severity (OR = 5.4, 95% CI 3.3-9.0). Conclusion: Patients with CSS spectrum disorders experience frequent pain and decreased quality of life. A high degree of CSS symptom severity is associated with negative experiences with healthcare providers, which deters the establishment of a positive provider-patient relationship. Further research is needed to help understand symptom severity in CSS and harness the power of the therapeutic alliance as a treatment modality.